Research on Tower Elevator Power Supply Mode Matching Maintenance Period and Wind Power Curtailment. (October 2019) - Wang, Fujing; Xie, Lirong; Zhang, Fang; Chao, Qin; Li, Jinwei
Abstract: In order to reduce the difficulty of maintenance and Increase the utilization of wind power, this paper proposes a new program of internal consumption. First of all, through the main influencing factors which contain wind speed and direction of theoretical wind power, building history NWP data and the mapping theory possible output reflection database; Secondly, using clustering method to screen the better consistency historical samples and neural network model to generate the power demand forecasting curve; Finally, the forecast curve of wasted wind power is matched with the maintenance downtime. Analysis of historical data of a wind farm in XinJiang region show that the power supply mode of consuming wasted wind power during maintenance time is feasible. This model can effectively improve the utilization rate of wind energy, it also provides reference for related research.